A Novel Analysis via Micro-CT Imaging Indicates That Chemically Modified Tetracycline-3 (CMT-3) Inhibits Tooth Relapse after Orthodontic Movement: A Pilot Experimental Study. (1st April 2019) - Vieira, Giovanni Modesto; Falcao, Denise Pinheiro; Queiroz, Sormani Bento Fernandes de; Lima, Valthierre Nunes de; Bentes de Azevedo, Ricardo; Tiziane, Valdenize; Moreno, Heitor; Amorim, Rivadavio
Abstract : Objective . To evaluate the effect of chemically modified tetracycline-3 (CMT-3) and simvastatin on tooth relapse after orthodontic movement in rats using a novel analysis method employing high-resolution micro-CT (Micro-CT) images. In addition, the correlation between bone density and orthodontic relapse was also evaluated for each experimental group. Methods . Forty adult male Wistar rats had stainless steel springs installed on their left upper first molars in order to generate tooth movement for 18 days. After this initial period, the animals were divided into three groups: (1) 30 mg/kg of CMT-3; (2) 5 mg/kg of simvastatin; and (3) 0.5% carboxymethylcellulose, and each group was treated for 20 days. Micro-CT images were analyzed (conventional method and 3D reconstruction) on the 7th and 18th days following spring fixation and finally, 20 days after treatment either with CMT-3 or simvastatin (38th day). Bone mineral density (BMD) of the mesial and distal roots of the upper first molar was also analyzed. Results . The difference was statistically significant between the groups as to recurrence (p = 0.048 ), and the post hoc test identified the value ofp = 0.007 between the control group and the CMT-3 group. Simvastatin was not able to inhibit tooth relapse. The bone mineral densities of both the mesial and distal roots were different between the three groups, after the 20th day of drug use (p = 0001 andp < 0001 ). Conclusion . Our findings support the initial evidence that CMT-3 is able to prevent relapse after tooth movement. Future trials in humans should evaluate such treatment as a promising approach to preventing this common phenomenon. Clinical Relevance . Considering the results obtained, CMT-3 can be used to avoid relapse after tooth movement.